지역사회 주민들의 주관적 건강인식과 행복지수의 관련성(2014년도 지역사회 건강조사 경남지역 자료이용) - 윤현서; Hyun Seo Yoon; 전진호; Jin-ho Chun; 채유정; You Jung Chae (대한구강보건학회지, 2017)
Objectives: Health is closely related to an individual`s assessment of their quality of life and their subjective level of happiness. The aim of this study was to investigate the association between happiness index and self-rated health by utilizing a community health survey in Korea. Methods: The study participants were 17,937 people living in Gyeongsangnam-do, Korea, who completed a community health survey in 2014. The non-subjective variables included in the statistical analysis were sex, age, region, education, income, and economic activity. The subjective awareness variables included self-rated health, self-rated oral health, chewing difficulty, pronunciation difficulty, and happiness index. Statistical analysis of the data was done using the SPSS 21.0 program. Results: Evaluation of the subjective awareness levels revealed that the respondents that were better educated, whose income levels were higher, and those who engaged in an economic activity found themselves to be in better physical health and oral health. In contrast, the respondents that were female, older, and with residence in the counties reported a higher incidence of chewing difficulty. There was a positive correlation between happiness index and subjective awareness level, and a negative correlation between chewing difficulty and pronunciation difficulty. Happiness index was influenced the most by subjective health levels, followed by income, age, pronunciation difficulty, subjective oral health, chewing difficulty, academic credential, region, and sex. Conclusions: Therefore, in order to improve the happiness index of community residents, regular health checkups and systematic oral health education should be prepared in order to improve awareness of subjective health and reduce discomfort in the oral cavity, and efforts should be made to reduce the gap between regions.